Vortex rings in axially rotating fluids - Terry, Helen (2019)
Rotating turbulent flows are found in many geophysical, astrophysical and industrial applications. These turbulent flows can be considered to be comprised of a collection of coherent structures. An understanding of these smaller coherent structures can allow insight into the behaviour of the larger turbulent motion as a whole. This thesis focuses on the effect of rotation on one particular type of coherent structure - the vortex ring - and is motivated by the belief that greater knowledge of how individual vortex rings behave in rotating fluids will lead to a better understanding of rotating turbulent flows.